Long-term trends in the incidence of depressive disorders in China, the United States, India and globally: A comparative study from 1990 to 2019 - Wang, Shuwen; Lu, Tianhuan; Sun, Jinyi; Huang, Lihong; Li, Ruiqing; Wang, Tong; Yu, Chuanhua (Frontiers in Psychology, 2023)
Background Depressive disorders have become an increasingly significant public health issue. This study is intended to show the trend of the incidence of depressive disorders in China, the United States, India and the world from 1990 to 2019, as well as the impact of age, period and cohort on it. Methods Extracting incidence data from the Global Burden of Disease Study 2019, we determined trends in the age-standardized incidence rate (ASIR) using Joinpoint regression. An age-period-cohort analysis was implemented to describe the effects of age, period, and cohort, as well as the long-term tendencies. Results From 1990 to 2019, the ASIR of depressive disorders in China was lower than that in the United States; India is lower than the United States in the first 5 years, showing a downward trend. The incidence in India and the United States is higher than the global average. The ASIR of women in the three countries is higher than that of men. In China, the elderly, early period and people born around 1954 have a higher risk of depressive disorders. In the United States, young people born around 1999 have a higher risk of depressive disorders. India is similar to China. Conclusion From 1990 to 2019, the age effect of China as a whole increased, and the period became stable, and the cohort effect declined. The overall age and period effects of the United States reduced, while the cohort effect increased. The age effect in India increased, while the period and cohort effects decreased. Depressive disorders are becoming ever more serious worldwide, and we’d better take measures to reduce its incidence according to the cohort effect of each age group.